Optimizing Red Light-Based Photodynamic Therapy for Effective Bactericidal Action Against Fusobacterium nucleatum Subspecies - Jianglan Li; Takayuki Nambu; Chao Wang; Hiroki Takigawa; Hugo Maruyama; Chiho Mashimo; Toshinori Okinaga (Pathogens)
Fusobacterium nucleatum (F. nucleatum), a key pathogen implicated in periodontal disease, contributes to oral biofilm maturation and is linked to development of systemic diseases like colorectal cancer and liver cirrhosis. Photodynamic therapy (PDT) combined with 5-aminolevulinic acid (5-ALA) treatment (ALA-PDT) selectively targets F. nucleatum by inducing porphyrin accumulation. The bactericidal effect of red light-based PDT on F. nucleatum has not been evaluated previously. This study investigates the effect of ALA-PDT using red light-emitting diode (LED) light on F. nucleatum subspecies and their porphyrin accumulation. F. nucleatum subspecies were cultured with varying concentrations of 5-ALA under anaerobic conditions. Porphyrin accumulation was measured via fluorescence spectroscopy, and colony-forming units were measured to determine bacterial viability post-treatment. Additionally, other subspecies responded well to 0.01% 5-ALA, and uroporphyrin I accumulation correlated with bacterial death, revealing optimal bactericidal conditions. These results suggest that optimizing light intensity and 5-ALA concentration can significantly enhance the therapeutic potential of ALA-PDT in oral healthcare.